2018
DOI: 10.1177/1559325818813066
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Whole-Body Vibration Exercises on Muscle Strength/Power and Bone of Elderly Individuals

Abstract: Beneficial effects are associated with whole-body vibration exercises (WBVEs). Increases in muscular strength/power, flexibility, and gait speed; improvements in bone mineral density, balance, and the quality of life; and decreased pain and risk of falls are reported. The aim is to present a review about the importance of WBVE for elderly individuals, considering clinical studies and meta-analyses, on bone and muscle strength/power. There is evidence supporting beneficial effect of WBVE in postmenopausal women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 48 publications
(95 reference statements)
1
33
0
Order By: Relevance
“…A favourable impact of whole-body VT [ 69 , 71 , 72 ] and local VT [ 38 , 73 ] on muscle strength was proposed by previous studies in healthy adults. This study found that it may also work in older adults with sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A favourable impact of whole-body VT [ 69 , 71 , 72 ] and local VT [ 38 , 73 ] on muscle strength was proposed by previous studies in healthy adults. This study found that it may also work in older adults with sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that better muscle strength and physical performance are more vulnerable to the ageing process than muscle mass [ 83 ]. Therefore, VT that can improve muscle strength and physical performance is critical for older adults with sarcopenia, which is associated with better ability to perform daily life activities and mobility, improvement in quality of life and reduced healthcare costs [ 72 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Pilates exercise improves more synthesis of muscle proteins and, therefore, a greater muscle mass content; it also increases bone mineral density in the body composition [30]. It is important to highlight that the percentage of muscle mass is lower in the older population than in adults [31]. In fact, strength-resistance training allows an increase in muscle mass content.…”
Section: Discussionmentioning
confidence: 99%
“…This type of activity, which can be generated with different platforms (vertical, rotational or lateral modes) (McMillan et al, 2017) generates forces that are transferred to the weight-bearing bones of the skeleton as done by other exercise modalities (Cheung and Giangregorio, 2012). So, WBV exercises could have beneficial effects associated with bone formation and the neuromuscular and cognitive functions, reducing the risk of falls and fractures (Moreira-Marconi et al, 2016; Bemben et al, 2018). However, several authors reported conflicting results due to the variety of protocols used (Marin-Puyalto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%